Patent cooperation treaty yearly review 2016 the international patent system (Geneva, Switzerland World Intellectual Property Organization, 2016)
Comprehensive facts, figures and analysis of the international patent system. Special Theme: the PCT market share. Datos completos, cifras y análisis del sistema internacional de patentes. Tema especial: la cuota de mercado del PCT (El Tratado de Cooperación en materia de Patentes).
Keywords: PATENTES -- DERECHOS; PATENTES DE INVENCION -- TRATADOS INTERNACIONALES